The Role of Market Orientation in Mediating Government Support on Export Performance of MSMEs Kopi Dampit Malang - Saraswati, Thusy Tiara; Sudarmiatin; Handayati, Puji (PT Maju Malaqbi Makkarana, 2025)
This study aims to analyze the influence of market orientation and government support on the export performance of coffee Micro, Small, and Medium Enterprises (MSMEs) in the Dampit region of Malang, and evaluate the mediating role of market orientation in the relationship between government support and export performance. The approach used was quantitative with survey method and path analysis to test the relationship between variables. The sample of this study amounted to 107 export Dampit coffee MSMEs. Data analysis techniques using descriptive statistics and SEM-PLS. The results showed that market orientation had a significant effect on export performance, while government support did not show a significant direct effect. However, government support was shown to significantly influence market orientation, and market orientation significantly mediated the relationship between government support and export performance. These findings reinforce the Resource-Based View (RBV) perspective, that the competitive advantage of MSMEs in the context of exports depends not only on external support, but also on the internal ability to understand the market and adapt to global dynamics. This research makes a theoretical contribution to the development of export entrepreneurship literature and offers practical implications for MSME actors and policy makers in designing market-oriented competitiveness strengthening strategies.